Features of using REST architecture for development of ARS for information systems - Sotnik, S. V. (ХНУРЕ, 2024)
The study explores key aspects of utilizing REST architecture for API development, particularly its impact on integration, scalability, and security of information systems. A model illustrating client-server interaction within context of REST is presented, along with detailed examination of practical advantages that enable efficient development of flexible and reliable systems. The role of REST in supporting microservice architecture and interface standardization is described, making it essential tool in modern software development.
Keywords: REST architecture; key features; information systems